ANALISIS PEMAHAMAN BAHASA LAMPUNG TERHADAP PENUTUR SMENDO - Wulandari , Desi; Putri, Melani Cindy (Jurnal Punyimbang, 2023)
Abstract This study aims to analyze the understanding of Lampung language among Smendo speakers, and to identify the factors that influence and challenges in preserving the language. A descriptive qualitative approach was used through in-depth interviews, field observations, and literature studies. The results of the study indicate that the understanding of Lampung language is greatly influenced by age, social environment, education, and technology. The older generation understands Lampung language better due to involvement in cultural traditions, while the younger generation dominates Indonesian due to the influence of formal education and social media. Linguistic assimilation in economic life results in a functional understanding of Lampung language, although limited to basic vocabulary. The main challenges include the lack of regional language education resources, weak individual motivation, and negative perceptions of the community who consider regional languages less relevant. Digital technology shows great potential in language preservation through creative content such as learning videos, mobile applications, and cultural campaigns on social media. This study recommends strengthening regional language education through teacher training and innovative teaching materials, utilizing technology to attract the younger generation, and empowering local communities. In addition, the integration of Lampung language in the creative economy and tourism can increase public appreciation of regional languages. This strategy is expected to support the preservation of the Lampung language in a sustainable manner and strengthen the cultural identity of the community amidst modernization.   Abstak Penelitian ini bertujuan untuk menganalisis pemahaman bahasa Lampung di kalangan penutur Smendo, serta mengidentifikasi faktor-faktor yang memengaruhi dan tantangan dalam pelestarian bahasa tersebut. Pendekatan kualitatif deskriptif digunakan melalui wawancara mendalam, observasi lapangan, dan studi literatur. Hasil penelitian menunjukkan bahwa pemahaman bahasa Lampung sangat dipengaruhi oleh usia, lingkungan sosial, pendidikan, dan teknologi. Generasi tua lebih memahami bahasa Lampung karena keterlibatan dalam tradisi budaya, sedangkan generasi muda lebih mendominasi bahasa Indonesia akibat pengaruh pendidikan formal dan media sosial. Asimilasi linguistik dalam kehidupan ekonomi menghasilkan pemahaman fungsional terhadap bahasa Lampung, meskipun terbatas pada kosakata dasar. Tantangan utama meliputi minimnya sumber daya pendidikan bahasa daerah, lemahnya motivasi individu, dan persepsi negatif masyarakat yang menganggap bahasa daerah kurang relevan. Teknologi digital menunjukkan potensi besar dalam pelestarian bahasa melalui konten kreatif seperti video pembelajaran, aplikasi mobile, dan kampanye budaya di media sosial. Penelitian ini merekomendasikan penguatan pendidikan bahasa daerah melalui pelatihan guru dan materi ajar inovatif, pemanfaatan teknologi untuk menarik generasi muda, dan pemberdayaan komunitas lokal. Selain itu, integrasi bahasa Lampung dalam ekonomi kreatif dan pariwisata dapat meningkatkan apresiasi masyarakat terhadap bahasa daerah. Strategi ini diharapkan mampu mendukung pelestarian bahasa Lampung secara berkelanjutan dan memperkuat identitas budaya masyarakat di tengah modernisasi.